Perancangan Ulang Tampilan Aplikasi Perpustakaan Digital ISOLOKKAB Berbasis Design Thinking - Irrisandi, Nadya Putri; Erlianti, Gustina (Lembaga Yasin AlSys, 2024)
Redesigning the appearance of the application is the process of redesigning the existing design with the aim of improving the user experience. This is due to the appearance of the application that is still behind compared to other applications. The purpose of this redesign is to produce an improved display that has been redesigned as a recommendation for the development of the iSolokKab digital library application. This redesign was carried out using interview techniques to iSolokKab application users and reviews from users from the Play Store. iSolokKab needs improvement both from the appearance design and features. The method used in this redesign process is the design thinking method. Design thinking is a method that focuses on user complaints and provides suitable solutions to problems experienced by users in the application. Therefore, this method is very suitable for the process of redesigning the appearance of this iSolokKab application, because it can understand user needs. Based on the results of tests that have been carried out on improving the appearance design of the iSolokKab application, it can be said that it is easy to understand by users, judging from the tests conducted on 5 respondents with an average time spent on each task of 9.6 seconds and no click errors. As a result, the process of redesigning this display design is fairly well understood by users because users can complete tasks easily. The redesign of the appearance of the iSolokKab application is expected to be a reference and improve the quality of the performance of the iSolokKab application itself.